Legal Certanity Of Land Disputes: Differences In The Assessment Of Evidence Of Realease Of Rights Between The Court Of Appeal And Cassation (Study Of Decision No 292/PDT/2018/PT.DKI And Decision No 212 K/PDT/2020) - Azkia Rihadatul Aisy (Semarang State University Undergraduate Law and Society Review, 2025)
In land practice in Indonesia, there are still many land sale and purchase transactions that are carried out without a land title certificate and are only based on a Letter of Release of Rights (SPH). As in Decision No. 595/PDT/2018/PT.DKI and Decision No. 212 K/Pdt/2020. This writing aims to analyze the differences in the assessment of evidence of the Letter of Release of Rights (SPH) by the Court of Appeal and the Supreme Court and assess its impact on the legal certainty of land ownership. This research uses a normative juridical method with the approach of legislation and decision studies. The results showed that the Court of Appeal considered that the Surat Pelepasan Hak (SPH) was not a valid proof of ownership because it did not meet the formal administrative requirements, while the Supreme Court considered the Surat Pelepasan Hak (SPH) to be legally valid because it was supported by the facts of physical possession, payment in full, and good faith.